An army crossing a one-log bridge - Ma, M (2001)
﻿ This thesis studies the place of English in middle school students' educational experiences in China by describing students' encounters with English and their experiences of English learning in both the formal and the informal situations. Observations, semi-structured oral and written interviews are conducted to investigate students' perceptions of English and their reflections on English learning. Open-ended surveys are used to explore the interactions between students' learning experiences and their life aspirations. The study seeks to identify important themes in English learning in China, and in particular, how students' reflections influence their learning and how their experiences shape their perceptions. It attempts to interpret the meaning of English learning at the public and private levels and to examine the convergence and conflict of learning needs and teaching agenda. To encourage the learner perspective in students' own voice in the discourse of English language teaching, the study heavily draws on students' personal statements. The study identified the quantification of education through examination and the mediation of English in changing ideas and shaping identity as two important themes in the learning of English language in China. While students' perception of English as a tool appears highly instrumental in nature, their motivation of learning for self-improvement reflects the dominant belief in science and technology in China. Such contradictions contribute to the situation in which formal learning organised according to the public agenda for national modernisation does not always meet students' individual needs for personal improvement. In addition, learner autonomy emerged as a crucial factor in making English learning a personally engaging and enriching experience. The study confirmed the importance of self-reflection on English learning by learners and all those concerned with English learning.